2005
DOI: 10.1113/jphysiol.2005.085043
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase II protein content is a determinant of exercise endurance capacity in the mouse

Abstract: Hexokinase (HK) II content is elevated in fatigue resistant muscle fibres and exercise trained muscle. The aim of this study was to determine if exercise capacity is dependent on muscle HK protein content. C57Bl/6 mice with a 50% HK knockout (HK +/− ), no genetic manipulation (wild-type, WT) and an ∼3-fold HK overexpression (HK Tg ) were tested. Mice (n = 12/group) completed both a maximal oxygen consumption (V O 2 ,max ) test and an endurance capacity test (run at ∼75%V O 2 ,max ) on an enclosed treadmill equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 43 publications
5
40
0
1
Order By: Relevance
“…Interestingly, the premature fatigue was closely correlated with exercise-stimulated MGU, and thus endurance capacity and MGU may be linked in the mouse. We previously reported that skeletal muscle HK II content, exercise-stimulated MGU, and exercise endurance capacity are closely correlated (6). Here we show that high-fat feeding, which impairs exercisestimulated MGU by 50%, is associated with a 40% reduction in endurance time in the mouse.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Interestingly, the premature fatigue was closely correlated with exercise-stimulated MGU, and thus endurance capacity and MGU may be linked in the mouse. We previously reported that skeletal muscle HK II content, exercise-stimulated MGU, and exercise endurance capacity are closely correlated (6). Here we show that high-fat feeding, which impairs exercisestimulated MGU by 50%, is associated with a 40% reduction in endurance time in the mouse.…”
Section: Discussionmentioning
confidence: 56%
“…Procedures were approved by the Vanderbilt University Animal Care and Use Committee. Male Ukko1 (a mixture of BALB/c and DBA/2 strains) mice containing a partial deletion to the HK II gene (HK ϩ/Ϫ ) that results in a 50% reduction in HK II activity in heart, skeletal muscle, and adipose tissue, but does not change HK I activity (5), were backcrossed onto the C57BL/6J background for at least five generations (6). At 3 weeks of age, littermates were separated by sex and maintained in microisolator cages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle glucose uptake during muscle contractions is dependent on hexokinase II and GLUT4 (29,30), but the expression of these proteins was not altered in β1β2M-KO mice (Fig. 4G).…”
Section: Ampk β1β2m-ko Mice Have Reduced Skeletal Muscle Glucose Uptakementioning
confidence: 99%
“…In many tissues including skeletal muscle, GLUT1 and GLUT4 predominate, with GLUT4 translocation to the plasma membrane and t tubules considered rate-limiting for the uptake of glucose in response to stimuli such as muscle contraction and insulin; however, it should be noted that under some situations, glucose phosphorylation by hexokinase also appears to be important (154,155). Importantly, during exercise and/or skeletal muscle contraction, glucose uptake is increased, an effect which is independent of the proximal part of the insulin signaling pathway (for review, see Ref.…”
Section: A Glucose Uptakementioning
confidence: 99%